OP0052 Prevalence and Physical and Mental Health Patterns of Rheumatic and Musculoskeletal Diseases in Portugal: Results from Epireumapt, A National Health Survey. (9th June 2015) - Branco, J.; Rodrigues, A.M.; Gouveia, N.; Pereira, L.; Eusébio, M.; Ramiro, S.; Machado, P.; Mourão, A.F.; Silva, I.; Laires, P.; Sepriano, A.; Araújo, F.; et al.
Abstract : Background: Rheumatic and musculoskeletal diseases (MSKD) are a prevalent leading cause of disability and consume a large amount of healthcare and social resources. MSKD have been associated with low levels of physical and mental health in other countries. Objectives: To estimate the national prevalence of hand, knee and hip osteoarthritis (OA), low back pain (LBP), rheumatoid arthritis (RA), fibromyalgia (FM), gout, spondyloarthritis (SpA), periarticular disease (PD) systemic lupus erythematosus (SLE), polymyalgia rheumatica (PMR) and osteoporosis (OP)) in the adult Portuguese population; to compare physical and mental health between participants with and without MSKD. Methods: EpiReumaPt is a national health survey conducted from Sep'2011 to Dec'2013, which involved a three-stage approach. First, 10661 adult subjects were randomly selected. Trained interviewers undertook structured face-to-face questionnaires in participant's households that included a screening for MSKD, and the EQ5D and HAQ. Secondly, all participants screened positive for at least one MSKD plus 20% of individuals with no rheumatic complaints were invited to be seen by a rheumatologist at the local Primary Care Center for a structured evaluation. Finally, a team of 3 experienced rheumatologists revised all the clinical data and confirmed the diagnoses according to previously validated criteria. Estimates were computed as weighted proportions, in order to take into account the sampling design. Results: Prevalence of MSKD in the adult Portuguese population is presented in Table 1 with 95% CI. After adjustment, subjects with RMD had significantly lower EQ5D scores (β=-0.09; p<0.001) and higher HAQ scores (β=0.12; p<0.001) than subjects with no MSKD. Some MSKD were significantly and independently associated with worse EQ5D scores: PMR (β=-0.334), RA (β=-0.132), FM (β=-0.100), LBP (β=-0.07), Knee OA (β=-0.06) and PD (β=-0.04). Proportion of anxiety and depression symptoms among the MSKD Portuguese patients was 16.7% and 8.3%, respectively; the prevalence of anxiety symptoms was significantly higher when compared with subjects without MSKD diseases (OR=3.4; p=0.003). Moreover, FM (OR=3.12; p<0.001), SpA (OR=2.82; p=0.012) and LBP (OR=1.84; p=0.007) were significantly and independently associated with the presence of anxiety symptoms; PMR (OR=18.81; p=0.006), FM (OR=3.73; p=0.001) and LBP (OR=1.55; p=0.030) were significantly and independently associated with the presence of depression symptoms. Conclusions: MSKDs are highly prevalent in Portugal and are associated with significant impairment of physical and mental health. Disclosure of Interest: J. Branco: None declared, A. Rodrigues: None declared, N. Gouveia: None declared, L. Pereira: None declared, M. Eusébio: None declared, S. Ramiro: None declared, P. Machado: None declared, A. Mourão: None declared, I. Silva: None declared, P. Laires Employee of: Merck, A. Sepriano: None declared, F. Araújo: None declared, S. Gonçalves: None declared, P. Coelho: None declared, V. Tavares: None declared, J. Cerol: None declared, J. Mendes: None declared, L. Carmona: None declared, H. Canhão: None declared